Pengaruh Rasio CAMEL Pada Praktik Manajemen Laba di Bank Perkreditan Rakyat Provinsi Bali - KUSUMA DEWI, LUH GEDE (E-Jurnal Akuntansi, 2013)
This research aims to examine the effect of the CAMEL’s ratios (indicated by the ratio of CAR, RORA, ROA, NPM and LDR) on the practice of earnings management (measured by discretionary accruals) in BPR on Bali Province. Purposive sampling produced final sample as many as 632 quarterly financial statements published by 79 BPR. This study used a multiple regression. The analysis showed that ratio of RORA and LDR effect on earnings management practices. Only two hypothesis was accepted, and on average there were conclude indications that earnings management practices influenced CAMEL ratios.
Keywords: Bali, BPR, CAMEL, earnings management, quarterly